Pengolahan dan Analisis Data Untuk Mendukung Program Desa Cinta Statistik di Desa Sokawera - Alya Fauziyah; Ria Novita Awalia Ramadhani; Ernawati Prahesta Kurnia Sari (LPPM IT Telkom Purwokerto, 2024)
Sokawera Village, Patikraja Sub-district, Banyumas Regency is one of the villages designated as an example of Desa Cinta Statistik (Desa Cantik). Desa Cantik data collection activities have been carried out using a survey with a paper questionnaire. The problem is that the results of the survey questionnaire have not been tabulated and analyzed due to the limited ability of village staff in data processing. The purpose of this community service is to assist Sokawera Village in processing the results of the Desa Cantik program survey. The methods used include observation and preparation, coordination, data collection, formatting, data entry, data validation, data tabulation, and descriptive analysis. Based on the descriptive analysis that has been carried out, Sokawera Village, which consists of 15 RT and 4 RW, has a total population of 3215 residents with 1602 male and 1603 female residents. In addition, data on social information of family members, education, births and deaths, health, business, land and livestock tenure, asset ownership, government development and security were also obtained. This PKM-PM program is expected to assist Sokawera Village in processing the results of the Desa Cantik program survey and have a positive impact involving an increased understanding of the social, economic and welfare conditions of the population, as well as opening up opportunities for the preparation of more targeted programs to improve the quality of life of the Sokawera Village community in a sustainable manner.